Pengaruh Model Pembelajaran Simas Eric Terhadap Kemampuan Berpikir Kritis Siswa Pada Materi Jaringan Tumbuhan - Atoillah, Fahmi; Muttaqin, Muhammad; Sholikha, Mar’atus (Jurnal Pendidikan Indonesia, 2022)
Abstracts written in Indonesian with a maximum of 250 words. Times New Roman, 12, justify text. Abstract contains a brief research background, the novelty and the significance of research, the purpose of research, a brief research method, a brief results of the research, and conclusions.